APPLICATION OF PLANT ESSENTIAL OILS FOR IMPROVING AIR QUALITY IN THE LECTURE-HALLS OF UNIVERSITIES - Bilyk, Tetiana; Lukianenko, Nataliia; Vityk, Karina; Havryliuk, Olesia (Proceedings of National Aviation University (archive), 2018)
Purpose: The general goal of the article is to analyze air contamination of lecturer-halls by microorganisms and to investigate antimicrobial activity of plant essential oils for improvement of ecological state of indoor microflora. Methods: For determination of the total number of microorganisms and assessment of air microflora contamination, Sedimentation method (Koch’s Pour Plate method) was used. The colonies of microorganisms were calculated according to the V. Omelianskii rule. Statistical processing of data made on the Microsoft Office Exel (with adequacy 95%). Indicators of standard deviations were calculated by conventional procedures. The morphology of microorganisms was studied on microscope "Mikmed 2" (with zoom × 1500). The impact of plant essential oils on chosen strains of microorganisms (Staphylococcus aureus UCM B-904, Pseudomonas aeruginosa UCM В-907, Escherichia coli UCM B-906) was estimated with the help of disc-diffusion method. Results: The round, white, yellow with a matte or shiny surface and with a smooth edge of the colonies of microorganisms were identified during the investigation. By the morphological features, microorganisms were gram-negative bacilli or gram-positive cocci. It has been established that the efficiency of plant essential oils appears in small concentrations and during of its increasing it changes insignificantly. In the research of antimicrobial activity of essential oils with the help of disco-diffusion method, it has been determined that the essential oils of lavender and eucalyptus have antimicrobial activity against to all the strains investigated. Conclusions: It has been investigated that investigated essential oils (lavender, eucalyptus, and juniper) inhibit the microorganisms to increase in the concentrations 5-15 mcl/m3 and can be used as the effective method of air treatment. Based on the research, the essential oils of lavender and eucalyptus can be recommended to use after classes in the concentrations of 5 mcl/m3.